Investigating Asian Parti-colored bats using the BatTalk internet of things approach. (15th December 2020) - Lin, Yun-Wei; Yen, Tai-Hsiang; Chou, Cheng-Han; Lin, Yi-Bing; Lai, Wen-Shu
Abstract: Labor intensive visual observation has been used to study the activities of Asian parti-colored (APC) bats in the past. Through an Internet of Things (IoT) platform called BatTalk, we continuously monitor the APC bats population to investigate its compositional changes, life history, and environmental factors. BatTalk achieves the same goals as traditional visual observations with reduced man power and minimal interference to the bat activities. In particular, BatTalk automates the process to understand APC bats' regular annual life cycle history and estimate the percentage of the baby bats born and raised there, who would return to their original habitat in the coming year. This paper proposes an inexpensive manner to identify the bat habitats and bat movement paths by identifying the bat's ultrasonic signal strength and GPS position, and then show the information in a map. Our study indicates that for current BatTalk deployment, the wireless communication delays have small variance, and as long as the observer moves with a constant speed, even if he/she moves fast, the bats still can be accurately located.